A New Look at Diogenes of Oinoanda, Fr. 157 Smith - Smith, Martin Ferguson (Hyperboreus, 2019)
Fr. 157, discovered in 1969 and ﬁrst published as NF (New Fragment) 4, is part of Diogenes of Oinoanda’s treatise on old age, the only known work on this subject by an Epicurean writer. Despite the increase in the number of known fragments of Old Age from 19 in 1968 to 71 today, the work is the most lacunose of the three treatises in Diogenes’ inscription, a major reason for this being the way each of its 18-line columns is split between three horizontal courses of stones, which means that, when one of the now-scattered blocks is recovered, it never contains more than eight lines and usually fewer.The three courses of Old Age, the topmost ones of the inscription, are called A, B, and C. Fr. 157 is a B-block, and the text of its two columns was continued from a missing block or blocks in course A above, and continued on a missing block or blocks in course C below. The preserved text of col. I is not abundant, consisting only of seven line-endings, but there was a likely mention of arrogant behaviour encountered or, possibly, displayed by old people. Diogenes would have agreed with Cephalus in Plato Resp. 329 b–d and with Cicero Sen. 65 that there is no need for the old to suﬀer discontent, and that, if they are discontented, that is their fault.More of col. II is preserved, but the last letters of 7–8 are damaged or missing, and μεναι in 9 has hitherto caused much puzzlement. The editor reads δυν[ά]μεναι, referring to ψυχαί, which he restores before 7. He also considers what should be restored after διὰ τὴν cυνοῦcαν in 12. His preferred suggestion is φύ/cιν θνητήν, closely followed by θνη/τότητα. The themes of the passage are the inevitability of death, no matter how long we have lived, and the brevity of human life.